2018
DOI: 10.1016/j.jdiacomp.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Lower objectively measured physical activity is linked with perceived risk of hypoglycemia in type 1 diabetes

Abstract: Individuals with type 1 diabetes engage in less MVPA than those without diabetes despite similar self-reported levels, with the main barrier being perceived risk of hypoglycemia. Adults with type 1 diabetes require guidance to meet current PA guidelines and reduce cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
(19 reference statements)
3
18
2
Order By: Relevance
“…In fact, the accumulation of high MVPA scores may reduce overall barriers to PA practices; however, the "fear of hypoglycemia" was the only barrier's item that seemed to be unchanged by high levels of MVPA, as per our results. Given that the "fear of hypoglycemia" is the main barrier to PA (Jabbour et al, 2016;Keshawarz et al, 2018), it is still currently unclear which mode of PA may favor an appropriate glycemic balance among individuals with T1D. Consistent with our results, a meta-analysis by Hasan et al (2018) in laboratorybased settings reported that among adults with T1D, engaging in moderate exercise appears to be associated with a high risk of hypoglycemia, and high-intensity exercise may be safer because of a lower decline in blood glucose.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In fact, the accumulation of high MVPA scores may reduce overall barriers to PA practices; however, the "fear of hypoglycemia" was the only barrier's item that seemed to be unchanged by high levels of MVPA, as per our results. Given that the "fear of hypoglycemia" is the main barrier to PA (Jabbour et al, 2016;Keshawarz et al, 2018), it is still currently unclear which mode of PA may favor an appropriate glycemic balance among individuals with T1D. Consistent with our results, a meta-analysis by Hasan et al (2018) in laboratorybased settings reported that among adults with T1D, engaging in moderate exercise appears to be associated with a high risk of hypoglycemia, and high-intensity exercise may be safer because of a lower decline in blood glucose.…”
Section: Discussionsupporting
confidence: 84%
“…These barriers have been evaluated using the Barriers to Physical Activity in Type 1 Diabetes (BAPAD-1) scale (Dubé et al, 2006;Brazeau et al, 2008Brazeau et al, , 2012b, and fear of hypoglycemia was identified as the main barrier to PA practices in adults (Brazeau et al, 2008) as well as in youth (children and adolescents) (Jabbour et al, 2016). Recently, a cross-sectional study conducted in diabetes adults supports the assumption that PA may be lower in this population due to unique barriers (Keshawarz et al, 2018). Unfortunately, reporting potential barriers, particularly fear of hypoglycemia in relation to PA levels is limited to cross-sectional studies, and no data are available whether any changes in scores for fear of hypoglycemia and/or overall perceived barriers scores over time will affect PA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines recommend that adults with type 1 diabetes should engage in 150 min or more of moderate-tovigorous-intensity physical activity (MVPA), spread over at least 3 days/week, with no more than 2 consecutive days without activity [9]. Despite this recommendation, it would appear that the majority of adults with type 1 diabetes do not meet this level of PA [2,5,7,[10][11][12][13]. Several barriers to exercise in type 1 diabetes have been identified [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several barriers to exercise in type 1 diabetes have been identified [14]. One of the main barriers to PA in children, adolescents [15], and adults [12,14,16] with type 1 diabetes is fear of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…The physicians and researchers selected patients using the following inclusion criteria: (1) 20–80 years old; and (2) ≥6 months since a diagnosis of diabetes. As well as patients with type 2 diabetes, we included patients with type 1 diabetes, because MVPA is recommended for both disease types (Colberg et al ., 2016) and patients with both types tend to exhibit low physical activity levels (Keshawarz et al ., 2018; Resnick et al ., 2006). The exclusion criteria were (1) HbA1c > 10.0%; (2) exercise restriction due to the progression of diabetic complications (e.g., retinopathy, diabetic nephropathy stage 4–5); (3) change in antidiabetic medication during the survey period; and (4) walking difficulty.…”
Section: Methodsmentioning
confidence: 99%